2017
DOI: 10.18520/cs/v113/i09/1729-1738
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variations in Pathogenic Bacteria in the Surface Sediments of the Zuari Estuary, Goa, India

Abstract: Estuaries are hotspots of anthropogenic activities. The deposition of pathogenic bacteria in the sediment and their re-suspension into the water column are influenced by riverine discharge and tides. The abundance of Escherichia coli O157:H7, Shigella spp., Salmonella spp., total coliforms (TC) and Vibrio spp. (Vibrio cholerae (VC), Vibrio parahaemolyticus (VP), Vibrio alginolyticus (VA)) was assessed along with the total bacterial count (TBC) and total viable count (TVC) in surface sediments along the banks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Typically, bacteria in aquatic environments are strongly associated with particulate matter. The association of bacteria is stronger in finer sediments and is strongly influenced by the quantity and type of clay minerals and organic matter (Hassard et al 2016;Gardade and Khandeparker 2017). The attachment of fecal coliforms to the fine particles increases their viability and transport to the sediment bed (Fries et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, bacteria in aquatic environments are strongly associated with particulate matter. The association of bacteria is stronger in finer sediments and is strongly influenced by the quantity and type of clay minerals and organic matter (Hassard et al 2016;Gardade and Khandeparker 2017). The attachment of fecal coliforms to the fine particles increases their viability and transport to the sediment bed (Fries et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Salinity has been identified as an additional driver of pathogen composition in estuaries, especially among Vibrio spp. [19,190]. However, studies have demonstrated that this relationship is not linear when salinities vary widely [191,192].…”
Section: Discussionmentioning
confidence: 99%
“…Along the Zuari estuary on the central west coast of India and during three seasons (pre-monsoon, monsoon, and post-monsoon), organic matter determined the distribution of Vibrio spp., with high values during the monsoon, probably due the terrestrial runoff [53]. In Guinea Bissau, the abundance of Vibrio spp.…”
Section: Nichementioning
confidence: 99%